Preparation method of foamy copper-based adsorption material for treating mercury ion-containing sewage

By loading benzyl cyanodiisocyanate on the surface of the foamed copper matrix and carrying out polycondensation reaction, a quadrixime benzyl cyanodithiol biphenyl adsorption material with wide pH adaptability and high mercury ion adsorption efficiency was prepared, and the prior art was solved The problems of low adsorption efficiency and narrow pH adaptability of Hg2+ achieve efficient removal and interference suppression of Hg2+.

CN119114038APending Publication Date: 2024-12-13NORTH CHINA UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411379089.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing adsorption materials have narrow adaptability to the pH value of Hg2+, and the adsorption and removal efficiency of Hg2+ ions is low, and it cannot effectively suppress the adsorption interference of other metal ions on Hg2+.

Method used

By loading benzyl diisocyanate on the surface of the foamed copper matrix, dichlorobiphenyl polycondensation reaction is carried out to form benzyl dichlorobiphenyl polyurea, and the substitution of thiol groups by chlorine and formation of amidoxime groups is prepared Amidoxime bendimercaptobiphenylidene adsorption material with excellent mercury ion adsorption properties.

Benefits of technology

It realizes efficient adsorption of Hg2+ ions in a wide pH range, and effectively suppresses the adsorption interference of other metal ions on Hg2+, improving the efficiency of mercury ion removal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114038A_ABST
    Figure CN119114038A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a foamy copper-based adsorbing material for treating mercury ion-containing sewage. The preparation method comprises the following steps in sequence: (1) loading benzonitrile diisocyanate on the surface of a foamy copper matrix; (2) the cyanobenzene diisocyanate on the surface of the foamy copper matrix is converted into cyanobenzene dichloro biphenyl polyurea through condensation polymerization with dichloro biphenyl; and (3) converting the cyanobenzene dichloro biphenyl polyurea into amidoxime benzene dimercapto biphenyl polyurea through substitution of chlorine by a mercapto group and formation of an amidoxime group, thereby finally obtaining the adsorption material. The adsorption material prepared by the method has excellent mercury ion adsorption removal efficiency and wide pH range adaptability, and can effectively inhibit the adsorption interference phenomenon of other metal ions on mercury ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of adsorption materials for wastewater treatment, in particular to a method for preparing a foam copper-based adsorption material for treating wastewater containing mercury ions. Background Art

[0002] Mercury and its compounds are biologically toxic and can easily cause serious threats to human health and the ecological environment through migration and accumulation in the food chain. Mercury and its compounds can be divided into metallic mercury, inorganic mercury and organic mercury. 2+ It has high solubility and is persistently cytotoxic and carcinogenic. A large amount of Hg is generated during the production and use of chlorine-alkali, batteries, mining and metallurgy, electrical appliances, paints, and medical instruments. 2+ Sewage, therefore, contains Hg 2+ Effective treatment of sewage is an inevitable requirement for achieving environmental protection and meeting sustainable development goals. 2+ The main sewage treatment methods include chemical precipitation, electrolysis-coagulation, membrane separation and adsorption. Among them, the chemical precipitation process requires the addition of chemical reagents and the precipitation will produce secondary pollution; the electrolysis-coagulation method not only produces secondary pollution but also requires electricity to drive the electrolysis reaction; the membrane separation technology is expensive and has high sensitivity to Hg 2+ The selectivity is not ideal. Adsorption method is used to treat Hg 2+ The ion wastewater process is simple, does not require external reagents and driving energy, and is a Hg 2+ The ideal direction for large-scale treatment of ion wastewater. However, existing adsorption materials are 2+ The pH value adaptability of effective adsorption treatment is narrow, Hg 2+ The ion adsorption removal efficiency is low, and it cannot effectively inhibit the removal of Hg by other metal ions. 2+ adsorption interference. Summary of the invention

[0003] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a foam copper-based adsorption material for treating wastewater containing mercury ions. The adsorption material prepared by the method has excellent mercury ion adsorption and removal efficiency, adaptability to a wide pH range, and can effectively inhibit the adsorption interference of other metal ions on mercury ions.

[0004] The technical solution adopted by the present invention to solve the technical problem is:

[0005] The present invention provides a method for preparing a foam copper-based adsorption material for treating wastewater containing mercury ions, comprising the following steps performed in sequence:

[0006] Step [1]: loading benzocyanate diisocyanate on the surface of the copper foam substrate;

[0007] Step [2] converting benzocyanate diisocyanate on the surface of the copper foam substrate into benzocyanate dichlorobiphenyl polyurea through a polycondensation reaction with dichlorobiphenyl;

[0008] Step [3] converts the benzocyandichlorobiphenyl polyurea into amidoximephenyl dimercaptobiphenyl polyurea by replacing chlorine with a mercapto group and forming an amidoxime group, thereby finally obtaining the adsorbent material.

[0009] Preferably, the step [1] specifically includes the following operations:

[0010] a1. Add dimethyl carbonate and toluene diisocyanate to diethylene glycol and mix to form a first mixed solution; add acetamide and urea to deionized water and mix to form a second mixed solution; add a certain amount of the first mixed solution to the second mixed solution and mix to form a synthetic solution; add 98% concentrated sulfuric acid and aminosulfonic acid to deionized water and mix to form an added solution;

[0011] a2. Immerse the copper foam sample in the synthetic solution, heat it to 60-85°C in a water bath, react at a constant temperature for 3-5 hours, then add a certain amount of additive solution to the synthetic solution, react at a constant temperature of 60-85°C for 1-2 hours, take out the sample and wash it with ethanol for several times, dry it at room temperature for 6-8 hours, and obtain copper foam with benzocyanate diisocyanate loaded on the surface, which is recorded as intermediate A.

[0012] Preferably, in step a1, the amount of dimethyl carbonate added to each liter of the first mixed solution is 40mL-70mL, and the amount of toluene diisocyanate added is 280mL-330mL; the concentration of acetamide in the second mixed solution is 120g / L-170g / L, and the concentration of urea is 50g / L-70g / L; the volume ratio between the first mixed solution and the second mixed solution in the synthetic solution is 2-3:1-2; the mass concentration of sulfuric acid in the additive solution is 3-8%, and the concentration of aminosulfonic acid is 10g / L-30g / L.

[0013] Preferably, in step a2, the weight of the foamed copper immersed in each liter of the synthetic liquid is 140-170 g; and the volume ratio between the added liquid and the synthetic liquid is 1-2:5-7.

[0014] Preferably, the step [2] specifically includes the following operations:

[0015] b1. Add 3,3'-dichlorobenzidine, azodicarbonamide and tert-butyl perbenzoate to a mixed solvent of glycerol and ethanol to form a polycondensation reaction solution;

[0016] b2. Immerse the intermediate A in the polycondensation reaction solution, heat to 45-60°C in a water bath under magnetic stirring, and react for 3-5 hours to complete the polycondensation reaction of benzocyanate diisocyanate and dichlorobiphenyl, and obtain a foam copper with benzocyanate dichlorobiphenyl polyurea loaded on the surface, which is recorded as intermediate B.

[0017] Preferably, the volume ratio of glycerol to ethanol in the mixed solvent is 1-2:3-4; the amount of 3,3'-dichlorobenzidine added to each liter of the polycondensation reaction liquid is 240-270 g, the amount of azodicarbonamide added is 50-70 g, and the amount of tert-butyl perbenzoate added is 20-40 mL.

[0018] Preferably, in step b2, the weight of the intermediate A immersed in each liter of the polycondensation reaction liquid is 80-130 g; and the stirring speed is 90-130 rpm.

[0019] Preferably, the step [3] specifically includes the following operations:

[0020] c1. Add ammonium thiosulfate and dimethyl sulfoxide to deionized water and mix to form a chlorine substitution solution; immerse the intermediate B in the chlorine substitution solution and allow the reaction to proceed at room temperature for 6-8 hours to complete the chlorine substitution process of the thiol group to obtain an intermediate C;

[0021] c2. Add hydroxylamine and ethylenediamine to deionized water and mix to form an amidoxime group-forming liquid; immerse the intermediate C in the amidoxime group-forming liquid and react at room temperature for 7-9 hours to complete the formation process of the amidoxime group, and obtain a foam copper with amidoximephenyl dimercaptobiphenyl polyurea loaded on the surface, which is the adsorption material.

[0022] Preferably, in step c1, the concentration of ammonium thiosulfate in the chlorine substitution liquid is 140 g / L-180 g / L, and the concentration of dimethyl sulfoxide is 70 mL / L-100 mL / L; the weight of the intermediate B immersed in each liter of the chlorine substitution liquid is 150-170 g.

[0023] Preferably, in step c2, the concentration of hydroxylamine in the amidoxime group-forming liquid is 210 g / L-230 g / L, and the concentration of ethylenediamine is 30 mL / L-60 mL / L; the weight of the intermediate C immersed in each liter of the amidoxime group-forming liquid is 70-90 g.

[0024] Positive effects of the present invention: The adsorbent material prepared by the method of the present invention is based on the condensation polymerization of benzocyanate and dichlorobiphenyl on the surface of the foam copper matrix to synthesize benzocyanate dichlorobiphenyl polyurea organic matter, and the nitrile group of benzocyanate dichlorobiphenyl polyurea is formed into amidoxime group and chlorine is replaced by mercapto group to obtain the foam copper adsorbent material loaded with amidoxime benzene dithiocarboxylic acid biphenyl polyurea on the surface. Based on the above structural characteristics, the polyurea structure enables the prepared adsorbent material to maintain stable chemical properties in a wide pH range; amidoxime group has soft base properties, because it has the property of reacting with soft acid Hg 2+ The strong tendency of ions to form complexes makes the adsorbent material highly selective for Hg adsorption 2+ ions; in addition, the thiol groups of the adsorbent material react with Hg 2+ Ions have a strong complexing effect and can effectively inhibit the binding of other metal ions to Hg 2+ Ion adsorption interference occurs.

[0025] In summary, the adsorption material prepared according to the present invention has excellent mercury ion adsorption and removal efficiency, wide pH range adaptability, and can effectively inhibit the adsorption interference of other metal ions on mercury ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the preparation process of the adsorption material of the present invention;

[0027] Figure 2 It is the structure of the amidoximephenyldimercaptobiphenyl polyurea of ​​the present invention;

[0028] Figure 3 It is the mercury ion adsorption removal rate in simulated mercury ion-containing wastewater under different pH conditions of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;

[0029] Figure 4 It is the adsorption removal rate of mercury ions in different simulated metal ion wastewater under the condition of pH 5 in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0030] Reference Figure 1 The present invention provides a method for preparing a foam copper-based adsorption material for treating wastewater containing mercury ions, comprising the following steps performed in sequence:

[0031] Step [1] loading benzyl cyanide diisocyanate on the surface of the copper foam substrate specifically comprises the following operations:

[0032] a1. Add dimethyl carbonate and toluene diisocyanate to diethylene glycol and mix to form a first mixed solution (the amount of dimethyl carbonate added per liter of the first mixed solution is 40mL-70mL, and the amount of toluene diisocyanate added is 280mL-330mL); acetamide and urea are added to deionized water to form a second mixed solution having an acetamide concentration of 120g / L-170g / L and a urea concentration of 50g / L-70g / L; the first mixed solution is added to the second mixed solution in a ratio of 2 to 3:1 to 2 by volume between the first mixed solution and the second mixed solution to form a synthetic solution; 98% concentrated sulfuric acid and sulfamic acid are added to deionized water to form a sulfuric acid concentration of 3-8% and a sulfamic acid concentration of 10g / L-30g / L.

[0033] a2. Immerse the copper foam sample in the synthetic solution (the weight of the copper foam immersed in each liter of the synthetic solution is 140-170 g), heat it in a water bath to 60-85°C, react at a constant temperature for 3-5 hours, add the additive liquid to the synthetic solution in a volume ratio of 1-2:5-7, react at a constant temperature of 60-85°C for 1-2 hours, take out the sample and wash it with ethanol for several times, and dry it at room temperature for 6-8 hours to obtain a copper foam with benzocyanate diisocyanate loaded on its surface, which is recorded as intermediate A.

[0034] Step [2] converts the benzocyanate diisocyanate on the surface of the copper foam substrate into benzocyanate dichlorobiphenyl polyurea through a polycondensation reaction with dichlorobiphenyl, which specifically includes the following operations:

[0035] b1. Add 3,3'-dichlorobenzidine, azodicarbonamide, and tert-butyl perbenzoate to a mixed solvent of glycerol and ethanol to form a polycondensation reaction liquid; wherein the volume ratio of glycerol to ethanol in the mixed solvent is 1 to 2:3 to 4; the amount of 3,3'-dichlorobenzidine added per liter of the polycondensation reaction liquid is 240-270 g, the amount of azodicarbonamide added is 50-70 g, and the amount of tert-butyl perbenzoate added is 20-40 mL;

[0036] b2. Immerse the intermediate A in the polycondensation reaction solution (the weight of the intermediate A immersed in each liter of the polycondensation reaction solution is 80-130g), heat it in a water bath to 45-60°C under magnetic stirring conditions with a stirring speed of 90-130 rpm, and react for 3-5 hours to complete the polycondensation reaction of benzocyanate and dichlorobiphenyl, and obtain a foam copper with benzocyanate and dichlorobiphenyl polyurea loaded on the surface, which is recorded as intermediate B. The structural formula of the benzocyanate and dichlorobiphenyl polyurea is:

[0037]

[0038] Step [3] converts the benzocyanodichlorobiphenyl polyurea into amidoximephenyldithiodiphenyl polyurea by replacing chlorine with a mercapto group and forming an amidoxime group, which specifically comprises the following operations:

[0039] c1. Add ammonium thiosulfate and dimethyl sulfoxide to deionized water to form a chlorine-substituted solution having an ammonium thiosulfate concentration of 140 g / L-180 g / L and a dimethyl sulfoxide concentration of 70 mL / L-100 mL / L; immerse the intermediate B in the chlorine-substituted solution (the weight of the intermediate B immersed in each liter of the chlorine-substituted solution is 150-170 g), and soak the reaction at room temperature for 6-8 hours to complete the chlorine substitution process of the thiol group to obtain the intermediate C;

[0040] c2. Add hydroxylamine and ethylenediamine to deionized water, mix to form an amidoxime group forming solution with a hydroxylamine concentration of 210g / L-230g / L and an ethylenediamine concentration of 30mL / L-60mL / L; immerse the intermediate C in the amidoxime group forming solution (the weight of the intermediate C immersed in each liter of the amidoxime group forming solution is 70-90g), react at room temperature for 7-9 hours, complete the formation process of the amidoxime group, and obtain a foam copper with amidoxime phenyl dimercaptobiphenyl polyurea loaded on the surface, which is the adsorption material. Wherein, the structural formula of the amidoxime phenyl dimercaptobiphenyl polyurea is as follows: Figure 2 shown.

[0041] The preferred embodiments of the present invention are described below by way of example.

[0042] Example 1

[0043] Preferred embodiment 1 of the present invention provides a method for preparing a foam copper-based adsorption material for treating wastewater containing mercury ions, comprising the following steps performed in sequence:

[0044] Step [1] loading benzyl cyanide diisocyanate on the surface of the copper foam substrate specifically comprises the following operations:

[0045] a1. Dimethyl carbonate and toluene diisocyanate were added to diethylene glycol to form a first mixed solution (60 mL of dimethyl carbonate and 320 mL of toluene diisocyanate were added per liter of the first mixed solution); acetamide and urea were added to deionized water to form a second mixed solution having an acetamide concentration of 160 g / L and a urea concentration of 60 g / L; the first mixed solution was added to the second mixed solution in a ratio of 3:2 by volume to form a synthetic solution; 98% concentrated sulfuric acid and sulfamic acid were added to deionized water to form a sulfuric acid concentration of 5% and a sulfamic acid concentration of 25 g / L.

[0046] a2. Immerse the copper foam sample in the synthetic solution (the weight of the copper foam immersed in each liter of the synthetic solution is 160 g), heat it to 80°C in a water bath, react at a constant temperature for 5 hours, add the additive liquid to the synthetic solution at a volume ratio of 2:7, react at a constant temperature of 75°C for 2 hours, take out the sample and wash it three times with ethanol, and dry it at room temperature for 7 hours to obtain a copper foam with benzocyanate diisocyanate loaded on the surface, which is recorded as intermediate A.

[0047] Step [2] converts the benzocyanate diisocyanate on the surface of the copper foam substrate into benzocyanate dichlorobiphenyl polyurea through a polycondensation reaction with dichlorobiphenyl, which specifically includes the following operations:

[0048] b1. Add 3,3'-dichlorobenzidine, azodicarbonamide, and tert-butyl perbenzoate to a mixed solvent of glycerol and ethanol to form a polycondensation reaction solution; wherein the volume ratio of glycerol to ethanol in the mixed solvent is 2:3; per liter of the polycondensation reaction solution, 3,3'-dichlorobenzidine is added in an amount of 260g, azodicarbonamide is added in an amount of 60g, and tert-butyl perbenzoate is added in an amount of 40mL;

[0049] b2. The intermediate A is immersed in the polycondensation reaction liquid (the weight of the intermediate A immersed in each liter of the polycondensation reaction liquid is 120 g), heated to 50° C. in a water bath under magnetic stirring at a stirring speed of 120 rpm, and reacted for 4 hours to complete the polycondensation reaction of benzocyanate diisocyanate and dichlorobiphenyl, and obtain a foam copper with benzocyanate dichlorobiphenyl polyurea loaded on the surface, which is recorded as intermediate B.

[0050] Step [3] converts the benzocyanodichlorobiphenyl polyurea into amidoximephenyldithiodiphenyl polyurea by replacing chlorine with a mercapto group and forming an amidoxime group, which specifically comprises the following operations:

[0051] c1. Add ammonium thiosulfate and dimethyl sulfoxide to deionized water to form a chlorine-substituted solution having an ammonium thiosulfate concentration of 170 g / L and a dimethyl sulfoxide concentration of 90 mL / L; immerse the intermediate B in the chlorine-substituted solution (the weight of the intermediate B immersed in each liter of the chlorine-substituted solution is 160 g), and soak and react at room temperature for 7 hours to complete the chlorine-substituted process of the thiol group to obtain the intermediate C;

[0052] c2. Hydroxylamine and ethylenediamine are added to deionized water, and mixed to form an amidoxime group-forming solution having a hydroxylamine concentration of 220 g / L and an ethylenediamine concentration of 50 mL / L; the intermediate C is immersed in the amidoxime group-forming solution (the weight of the intermediate C immersed in each liter of the amidoxime group-forming solution is 80 g), and the reaction is carried out at room temperature for 8 hours to complete the formation process of the amidoxime group, and a foam copper having an amidoxime-phenylenedithiobiphenyl polyurea loaded on the surface is obtained, which is the adsorption material, recorded as Example 1.

[0053] Comparative Example 1

[0054] This comparative example 1 provides a method for preparing a foam copper-based adsorption material for treating wastewater containing mercury ions, comprising the following steps performed in sequence:

[0055] Step [1] loading benzyl cyanide diisocyanate on the surface of the copper foam substrate specifically comprises the following operations:

[0056] a1. Dimethyl carbonate and toluene diisocyanate were added to diethylene glycol to form a first mixed solution (50 mL of dimethyl carbonate and 290 mL of toluene diisocyanate were added per liter of the first mixed solution); acetamide and urea were added to deionized water to form a second mixed solution having an acetamide concentration of 130 g / L and a urea concentration of 55 g / L; the first mixed solution was added to the second mixed solution in a ratio of 2:1 by volume to form a synthetic solution; 98% concentrated sulfuric acid and sulfamic acid were added to deionized water to form a sulfuric acid concentration of 5% and a sulfamic acid concentration of 15 g / L.

[0057] a2. Immerse the copper foam sample in the synthetic solution (the weight of the copper foam immersed in each liter of the synthetic solution is 160 g), heat it to 75°C in a water bath, react at a constant temperature for 4 hours, add the additive liquid to the synthetic solution at a volume ratio of 2:5, react at a constant temperature of 70°C for 2 hours, take out the sample and wash it twice with ethanol, and dry it at room temperature for 6 hours to obtain a copper foam with benzocyanate diisocyanate loaded on its surface, which is recorded as intermediate A.

[0058] Step [2] converts the benzocyanate diisocyanate on the surface of the copper foam substrate into benzocyanate dichlorobiphenyl polyurea through a polycondensation reaction with dichlorobiphenyl, which specifically includes the following operations:

[0059] b1. Add 3,3'-dichlorobenzidine, azodicarbonamide, and tert-butyl perbenzoate to a mixed solvent of glycerol and ethanol to form a polycondensation reaction liquid; wherein the volume ratio of glycerol to ethanol in the mixed solvent is 1:3; per liter of the polycondensation reaction liquid, 3,3'-dichlorobenzidine is added in an amount of 255g, azodicarbonamide is added in an amount of 60g, and tert-butyl perbenzoate is added in an amount of 30mL;

[0060] b2. The intermediate A is immersed in the polycondensation reaction liquid (the weight of the intermediate A immersed in each liter of the polycondensation reaction liquid is 90 g), heated to 50° C. in a water bath under magnetic stirring at a stirring speed of 100 rpm, and reacted for 4 hours to complete the polycondensation reaction of benzocyanate diisocyanate and dichlorobiphenyl, and obtain a foam copper with benzocyanate dichlorobiphenyl polyurea loaded on the surface, which is recorded as intermediate B.

[0061] Step [3] converts the benzocyanate dichlorobiphenyl polyurea by replacing chlorine with a mercapto group, specifically comprising the following operations:

[0062] Ammonium thiosulfate and dimethyl sulfoxide are added to deionized water and mixed to form a chlorine substitution solution with an ammonium thiosulfate concentration of 150 g / L and a dimethyl sulfoxide concentration of 80 mL / L; the intermediate B is immersed in the chlorine substitution solution (the weight of the intermediate B immersed in each liter of the chlorine substitution solution is 155 g), and the immersion reaction is carried out at room temperature for 6 hours to complete the replacement process of chlorine by the thiol group, and the adsorption material (foam copper-based loaded benzocyandithiol biphenyl polyurea) is obtained, which is recorded as Comparative Example 1.

[0063] Comparative Example 2

[0064] This comparative example 2 provides a method for preparing a foam copper-based adsorption material for treating wastewater containing mercury ions, comprising the following steps performed in sequence:

[0065] Step [1] loading benzyl cyanide diisocyanate on the surface of the copper foam substrate specifically comprises the following operations:

[0066] a1. Add dimethyl carbonate and toluene diisocyanate to diethylene glycol and mix to form a first mixed solution (60 mL of dimethyl carbonate and 300 mL of toluene diisocyanate per liter of the first mixed solution); add acetamide and urea to deionized water and mix to form a second mixed solution having an acetamide concentration of 140 g / L and a urea concentration of 60 g / L; add the first mixed solution to the second mixed solution in a volume ratio of 3:2 to form a synthetic solution; add 98% concentrated sulfuric acid and sulfamic acid to deionized water and mix to form a sulfuric acid concentration of 5% and a sulfamic acid concentration of 20 g / L;

[0067] a2. Immerse the copper foam sample in the synthetic solution (the weight of the copper foam immersed in each liter of the synthetic solution is 160 g), heat it to 80°C in a water bath, react at a constant temperature for 5 hours, add the additive liquid to the synthetic solution at a volume ratio of 1:6, react at a constant temperature of 70°C for 2 hours, take out the sample and wash it three times with ethanol, and dry it at room temperature for 7 hours to obtain a copper foam with benzocyanate diisocyanate loaded on the surface, which is recorded as intermediate A.

[0068] Step [2] converts the benzocyanate diisocyanate on the surface of the copper foam substrate into benzocyanate dichlorobiphenyl polyurea through a polycondensation reaction with dichlorobiphenyl, which specifically includes the following operations:

[0069] b1. Add 3,3'-dichlorobenzidine, azodicarbonamide, and tert-butyl perbenzoate to a mixed solvent of glycerol and ethanol to form a polycondensation reaction liquid; wherein the volume ratio of glycerol to ethanol in the mixed solvent is 1:3; per liter of the polycondensation reaction liquid, 3,3'-dichlorobenzidine is added in an amount of 260g, azodicarbonamide is added in an amount of 60g, and tert-butyl perbenzoate is added in an amount of 30mL;

[0070] b2. The intermediate A is immersed in the polycondensation reaction liquid (the weight of the intermediate A immersed in each liter of the polycondensation reaction liquid is 120 g), heated to 50° C. in a water bath under magnetic stirring at a stirring speed of 100 rpm, and reacted for 4 hours to complete the polycondensation reaction of benzocyanate diisocyanate and dichlorobiphenyl, and obtain a foam copper with benzocyanate dichlorobiphenyl polyurea loaded on the surface, which is recorded as intermediate B.

[0071] Step [3] converts the benzocyanate dichlorobiphenyl polyurea through the formation of amidoxime groups, specifically comprising the following operations:

[0072] Hydroxylamine and ethylenediamine were added to deionized water and mixed to form an amidoxime group-forming liquid having a hydroxylamine concentration of 220 g / L and an ethylenediamine concentration of 50 mL / L; the intermediate B was immersed in the amidoxime group-forming liquid (the weight of the intermediate B immersed in each liter of the amidoxime group-forming liquid was 80 g), and the reaction was carried out at room temperature for 8 hours to complete the formation process of the amidoxime group, and the adsorption material (foam copper-based amidoxime-loaded phenyldichlorobiphenyl polyurea) was obtained, which was recorded as Comparative Example 2.

[0073] In order to analyze the mercury ion adsorption and removal performance and pH range adaptability of Example 1, Comparative Example 1 and Comparative Example 2 in treating mercury ion-containing wastewater, mercuric nitrate was added to deionized water to prepare simulated mercury ion-containing wastewater with a mercury nitrate concentration of 10 mg / L. The pH value of the simulated mercury ion-containing wastewater prepared above was adjusted with hydrochloric acid and sodium hydroxide to obtain simulated mercury ion-containing wastewaters with pH values ​​of 2, 3, 4, 5, 6, and 7. 30 g of the corresponding adsorption material (Example 1, Comparative Example 1, Comparative Example 2) was placed in each liter of the corresponding simulated wastewater for mercury ion adsorption treatment, and the treatment time was 40 min. The Hg content of the corresponding simulated wastewater after the adsorption treatment was measured by inductively coupled plasma emission spectrometer (ICP-OES). 2+ Concentration, calculated Hg 2+ Adsorption removal rate, the results are as follows Figure 3 As shown in Example 1, Hg 2+ The removal rates of Hg ions were higher than 92%, while the removal rates of Hg 2+ The removal rates of Hg ions were all lower than 40%, and the Hg 2+The removal rate of ions is significantly affected at different pH values.

[0074] In addition, in order to analyze the inhibition of other metal ions on Hg by Example 1, Comparative Example 1 and Comparative Example 2, 2+ Adsorption interference performance, mercuric nitrate, cadmium nitrate, copper sulfate and potassium dichromate were added to deionized water to form a Hg-containing solution with a mercury ion concentration of 10 mg / L. 2 Simulated sewage, mercury ion concentration is 10mg / L, Cd 2+ Ion concentration of 10mg / L containing Hg 2+ -Cd 2+ Simulated sewage, Hg 2+ The concentration is 10mg / L, Cu 2+ Ion concentration of 10mg / L containing Hg 2+ -Cu 2+ Simulated sewage, Hg 2+ The concentration is 10mg / L, Cr 6+ Concentration is 10mg / L containing Hg 2+ -Cr 6+ Ion simulated sewage, each simulated sewage prepared by adjusting the pH value of each simulated sewage with hydrochloric acid and sodium hydroxide to 5. 30g of adsorption material (Example 1, Comparative Example 1, Comparative Example 2) was placed in each liter of the corresponding simulated sewage for mercury ion adsorption treatment, and the treatment time was 40min. The mercury ion concentration of the corresponding simulated sewage after the adsorption treatment was measured by inductively coupled plasma optical emission spectrometer (ICP-OES), and the mercury ion adsorption removal rate was calculated. The results are as follows: Figure 4 As shown in Example 1, 2+ Ion wastewater, containing Hg 2+ -Cd 2+ Simulated sewage, containing Hg 2+ -Cu 2+ Simulated sewage and Hg 2+ -Cr 6+ Hg after 40 minutes of adsorption treatment of ion simulated sewage 2+ The ion removal rate is almost the same, reaching about 93%; Comparative Example 1 has a 2+ Ion wastewater, containing Hg 2+ -Cd 2+ Simulated sewage, containing Hg 2+ -Cu 2+ Simulated sewage and Hg 2+ -Cr 6+ Hg after 40 minutes of adsorption treatment of ion simulated sewage 2+ The ion removal rates were 35%, 26%, 22% and 24% respectively; 2+ Ion wastewater, containing Hg 2 +-Cd 2+ Simulated sewage, containing Hg 2+ -Cu 2+ Simulated sewage and Hg 2+ -Cr 6+ Hg after 40 minutes of adsorption treatment of ion simulated sewage 2+ The ion removal rates were 33%, 31%, 31% and 22% respectively. Obviously, Example 1 has the ability to inhibit the effects of other metal ions on Hg 2+ Characteristics of ion adsorption interferences.

[0075] In summary, the adsorption material prepared according to the present invention has excellent mercury ion adsorption and removal efficiency, wide pH range adaptability, and can effectively inhibit the adsorption interference of other metal ions on mercury ions.

[0076] To illustrate in further detail, three additional examples are provided below.

[0077] Example 2

[0078] Preferred embodiment 2 of the present invention provides a method for preparing a foam copper-based adsorbent material for treating wastewater containing mercury ions, comprising the following steps performed in sequence:

[0079] Step [1] loading benzyl cyanide diisocyanate on the surface of the copper foam substrate specifically comprises the following operations:

[0080] a1. Dimethyl carbonate and toluene diisocyanate were added to diethylene glycol to form a first mixed solution (40 mL of dimethyl carbonate and 280 mL of toluene diisocyanate were added per liter of the first mixed solution); acetamide and urea were added to deionized water to form a second mixed solution having an acetamide concentration of 120 g / L and a urea concentration of 70 g / L; the first mixed solution was added to the second mixed solution in a ratio of 3:1 by volume to form a synthetic solution; 98% concentrated sulfuric acid and sulfamic acid were added to deionized water to form a sulfuric acid concentration of 3% and a sulfamic acid concentration of 10 g / L.

[0081] a2. Immerse the copper foam sample in the synthetic solution (the weight of the copper foam immersed in each liter of the synthetic solution is 140 g), heat it to 85°C in a water bath, react at a constant temperature for 3 hours, add the additive liquid to the synthetic solution at a volume ratio of 2:5, react at a constant temperature of 60°C for 2 hours, take out the sample and wash it three times with ethanol, and dry it at room temperature for 6 hours to obtain a copper foam with benzocyanate diisocyanate loaded on the surface, which is recorded as intermediate A.

[0082] Step [2] converts the benzocyanate diisocyanate on the surface of the copper foam substrate into benzocyanate dichlorobiphenyl polyurea through a polycondensation reaction with dichlorobiphenyl, which specifically includes the following operations:

[0083] b1. Add 3,3'-dichlorobenzidine, azodicarbonamide, and tert-butyl perbenzoate to a mixed solvent of glycerol and ethanol to form a polycondensation reaction solution; wherein the volume ratio of glycerol to ethanol in the mixed solvent is 1:3; per liter of the polycondensation reaction solution, 3,3'-dichlorobenzidine is added in an amount of 240g, azodicarbonamide is added in an amount of 70g, and tert-butyl perbenzoate is added in an amount of 40mL;

[0084] b2. The intermediate A is immersed in the polycondensation reaction liquid (the weight of the intermediate A immersed in each liter of the polycondensation reaction liquid is 80 g), heated to 60° C. in a water bath under magnetic stirring at a stirring speed of 90 rpm, and reacted for 3 hours to complete the polycondensation reaction of benzocyanate diisocyanate and dichlorobiphenyl, and obtain a foam copper with benzocyanate dichlorobiphenyl polyurea loaded on the surface, which is recorded as intermediate B.

[0085] Step [3] converts the benzocyanodichlorobiphenyl polyurea into amidoximephenyldithiodiphenyl polyurea by replacing chlorine with a mercapto group and forming an amidoxime group, which specifically comprises the following operations:

[0086] c1. Add ammonium thiosulfate and dimethyl sulfoxide to deionized water to form a chlorine-substituted solution having an ammonium thiosulfate concentration of 140 g / L and a dimethyl sulfoxide concentration of 70 mL / L; immerse the intermediate B in the chlorine-substituted solution (the weight of the intermediate B immersed in each liter of the chlorine-substituted solution is 150 g), and soak and react at room temperature for 6 hours to complete the chlorine-substituted process of the thiol group to obtain the intermediate C;

[0087] c2. Add hydroxylamine and ethylenediamine to deionized water, mix to form an amidoxime group-forming solution having a hydroxylamine concentration of 210 g / L and an ethylenediamine concentration of 30 mL / L; immerse the intermediate C in the amidoxime group-forming solution (the weight of the intermediate C immersed in each liter of the amidoxime group-forming solution is 70 g), react at room temperature for 7 hours, complete the formation process of the amidoxime group, and obtain a foam copper with amidoximephenyl dimercaptobiphenyl polyurea loaded on the surface, which is the adsorption material.

[0088] Example 3

[0089] Preferred embodiment 3 of the present invention provides a method for preparing a foam copper-based adsorbent material for treating wastewater containing mercury ions, comprising the following steps performed in sequence:

[0090] Step [1] loading benzyl cyanide diisocyanate on the surface of the copper foam substrate specifically comprises the following operations:

[0091] a1. Add dimethyl carbonate and toluene diisocyanate to diethylene glycol and mix to form a first mixed solution (the amount of dimethyl carbonate added per liter of the first mixed solution is 70 mL, and the amount of toluene diisocyanate added is 330 mL); acetamide and urea are added to deionized water to form a second mixed solution having an acetamide concentration of 170 g / L and a urea concentration of 50 g / L; the first mixed solution is added to the second mixed solution in a ratio of 3:2 by volume between the first mixed solution and the second mixed solution to form a synthetic solution; 98% concentrated sulfuric acid and sulfamic acid are added to deionized water to form a sulfuric acid concentration of 8% and a sulfamic acid concentration of 30 g / L of the added solution;

[0092] a2. Immerse the copper foam sample in the synthetic solution (the weight of the copper foam immersed in each liter of the synthetic solution is 170 g), heat it to 60°C in a water bath, react at a constant temperature for 5 hours, add the additive liquid to the synthetic solution at a volume ratio of 1:7, react at a constant temperature of 85°C for 1 hour, take out the sample and wash it twice with ethanol, and dry it at room temperature for 8 hours to obtain a copper foam with benzocyanate diisocyanate loaded on the surface, which is recorded as intermediate A.

[0093] Step [2] converts the benzocyanate diisocyanate on the surface of the copper foam substrate into benzocyanate dichlorobiphenyl polyurea through a polycondensation reaction with dichlorobiphenyl, which specifically includes the following operations:

[0094] b1. Add 3,3'-dichlorobenzidine, azodicarbonamide, and tert-butyl perbenzoate to a mixed solvent of glycerol and ethanol to form a polycondensation reaction solution; wherein the volume ratio of glycerol to ethanol in the mixed solvent is 2:3; per liter of the polycondensation reaction solution, 3,3'-dichlorobenzidine is added in an amount of 270g, azodicarbonamide is added in an amount of 50g, and tert-butyl perbenzoate is added in an amount of 20mL;

[0095] b2. The intermediate A is immersed in the polycondensation reaction liquid (the weight of the intermediate A immersed in each liter of the polycondensation reaction liquid is 130 g), heated to 45° C. in a water bath under magnetic stirring at a stirring speed of 130 rpm, and reacted for 5 hours to complete the polycondensation reaction of benzocyanate diisocyanate and dichlorobiphenyl, and obtain a foam copper with benzocyanate dichlorobiphenyl polyurea loaded on the surface, which is recorded as intermediate B.

[0096] Step [3] converts the benzocyanodichlorobiphenyl polyurea into amidoximephenyldithiodiphenyl polyurea by replacing chlorine with a mercapto group and forming an amidoxime group, which specifically comprises the following operations:

[0097] c1. Add ammonium thiosulfate and dimethyl sulfoxide to deionized water to form a chlorine-substituted solution having an ammonium thiosulfate concentration of 180 g / L and a dimethyl sulfoxide concentration of 100 mL / L; immerse the intermediate B in the chlorine-substituted solution (the weight of the intermediate B immersed in each liter of the chlorine-substituted solution is 170 g), and soak and react at room temperature for 8 hours to complete the chlorine-substituted process of the thiol group to obtain the intermediate C;

[0098] c2. Add hydroxylamine and ethylenediamine to deionized water, mix to form an amidoxime group-forming liquid having a hydroxylamine concentration of 230 g / L and an ethylenediamine concentration of 60 mL / L; immerse the intermediate C in the amidoxime group-forming liquid (the weight of the intermediate C immersed in each liter of the amidoxime group-forming liquid is 90 g), react at room temperature for 9 hours, complete the formation process of the amidoxime group, and obtain a foam copper with amidoximephenyl dimercaptobiphenyl polyurea loaded on the surface, which is the adsorption material.

[0099] Example 4

[0100] Preferred embodiment 4 of the present invention provides a method for preparing a foam copper-based adsorbent material for treating wastewater containing mercury ions, comprising the following steps performed in sequence:

[0101] Step [1] loading benzyl cyanide diisocyanate on the surface of the copper foam substrate specifically comprises the following operations:

[0102] a1. Dimethyl carbonate and toluene diisocyanate were added to diethylene glycol to form a first mixed solution (55 mL of dimethyl carbonate and 305 mL of toluene diisocyanate were added per liter of the first mixed solution); acetamide and urea were added to deionized water to form a second mixed solution having an acetamide concentration of 145 g / L and a urea concentration of 60 g / L; the first mixed solution was added to the second mixed solution in a ratio of 2:1 by volume to form a synthetic solution; 98% concentrated sulfuric acid and sulfamic acid were added to deionized water to form a sulfuric acid concentration of 6% and a sulfamic acid concentration of 20 g / L.

[0103] a2. Immerse the copper foam sample in the synthetic solution (the weight of the copper foam immersed in each liter of the synthetic solution is 155 g), heat it to 75°C in a water bath, react at a constant temperature for 4 hours, add the additive liquid to the synthetic solution at a volume ratio of 2:5, react at a constant temperature of 70°C for 1.5 hours, take out the sample and wash it with ethanol for several times, dry it at room temperature for 7 hours, and obtain a copper foam with benzocyanate diisocyanate loaded on the surface, which is recorded as intermediate A.

[0104] Step [2] converts the benzocyanate diisocyanate on the surface of the copper foam substrate into benzocyanate dichlorobiphenyl polyurea through a polycondensation reaction with dichlorobiphenyl, which specifically includes the following operations:

[0105] b1. Add 3,3'-dichlorobenzidine, azodicarbonamide, and tert-butyl perbenzoate to a mixed solvent of glycerol and ethanol to form a polycondensation reaction solution; wherein the volume ratio of glycerol to ethanol in the mixed solvent is 2:3; per liter of the polycondensation reaction solution, 3,3'-dichlorobenzidine is added in an amount of 255g, azodicarbonamide is added in an amount of 60g, and tert-butyl perbenzoate is added in an amount of 30mL;

[0106] b2. The intermediate A is immersed in the polycondensation reaction liquid (the weight of the intermediate A immersed in each liter of the polycondensation reaction liquid is 105 g), heated to 50° C. in a water bath under magnetic stirring at a stirring speed of 110 rpm, and reacted for 4 hours to complete the polycondensation reaction of benzocyanate diisocyanate and dichlorobiphenyl, and obtain a foam copper with benzocyanate dichlorobiphenyl polyurea loaded on the surface, which is recorded as intermediate B.

[0107] Step [3] converts the benzocyanodichlorobiphenyl polyurea into amidoximephenyldithiodiphenyl polyurea by replacing chlorine with a mercapto group and forming an amidoxime group, which specifically comprises the following operations:

[0108] c1. Add ammonium thiosulfate and dimethyl sulfoxide to deionized water to form a chlorine-substituted solution having an ammonium thiosulfate concentration of 160 g / L and a dimethyl sulfoxide concentration of 85 mL / L; immerse the intermediate B in the chlorine-substituted solution (the weight of the intermediate B immersed in each liter of the chlorine-substituted solution is 160 g), and soak and react at room temperature for 7 hours to complete the chlorine-substituted process of the thiol group to obtain the intermediate C;

[0109] c2. Add hydroxylamine and ethylenediamine to deionized water, mix to form an amidoxime group-forming solution having a hydroxylamine concentration of 220 g / L and an ethylenediamine concentration of 45 mL / L; immerse the intermediate C in the amidoxime group-forming solution (the weight of the intermediate C immersed in each liter of the amidoxime group-forming solution is 80 g), react at room temperature for 8 hours, complete the formation process of the amidoxime group, and obtain a foam copper with amidoximephenyl dimercaptobiphenyl polyurea loaded on the surface, which is the adsorption material.

[0110] The above are only preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and core ideas of the present invention, and is not used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, etc. made within the ideas and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a foam copper-based adsorbent material for treating wastewater containing mercury ions, characterized in that: It contains the following steps in order: Step [1]: loading benzocyanate diisocyanate on the surface of the copper foam substrate; Step [2] converting benzocyanate diisocyanate on the surface of the copper foam substrate into benzocyanate dichlorobiphenyl polyurea through a polycondensation reaction with dichlorobiphenyl; Step [3] converts the benzocyandichlorobiphenyl polyurea into amidoximebenzenedithiobiphenyl polyurea by replacing chlorine with a mercapto group and forming an amidoxime group, thereby finally obtaining the adsorbent material.

2. The method for preparing a foam copper-based adsorbent material for treating wastewater containing mercury ions according to claim 1, characterized in that: The step [1] specifically includes the following operations: a1. Add dimethyl carbonate and toluene diisocyanate to diethylene glycol and mix to form a first mixed solution; add acetamide and urea to deionized water and mix to form a second mixed solution; add a certain amount of the first mixed solution to the second mixed solution and mix to form a synthetic solution; add 98% concentrated sulfuric acid and aminosulfonic acid to deionized water and mix to form an added solution; a2. Immerse the copper foam sample in the synthetic solution, heat it to 60-85°C in a water bath, react at a constant temperature for 3-5 hours, then add a certain amount of additive solution to the synthetic solution, react at a constant temperature of 60-85°C for 1-2 hours, take out the sample and wash it with ethanol for several times, dry it at room temperature for 6-8 hours, and obtain copper foam with benzocyanate diisocyanate loaded on the surface, which is recorded as intermediate A.

3. The method for preparing a foam copper-based adsorbent material for treating wastewater containing mercury ions according to claim 2, characterized in that: In step a1, the amount of dimethyl carbonate added to each liter of the first mixed solution is 40mL-70mL, and the amount of toluene diisocyanate added is 280mL-330mL; the concentration of acetamide in the second mixed solution is 120g / L-170g / L, and the concentration of urea is 50g / L-70g / L; the volume ratio between the first mixed solution and the second mixed solution in the synthetic solution is 2-3:1-2; the mass concentration of sulfuric acid in the additive solution is 3-8%, and the concentration of aminosulfonic acid is 10g / L-30g / L.

4. The method for preparing a foam copper-based adsorbent material for treating wastewater containing mercury ions according to claim 2, characterized in that: In step a2, the weight of the foamed copper immersed in each liter of the synthetic liquid is 140-170 g; and the volume ratio between the added liquid and the synthetic liquid is 1-2:5-7.

5. The method for preparing a foam copper-based adsorbent material for treating wastewater containing mercury ions according to claim 1, characterized in that: The step [2] specifically includes the following operations: b1. Add 3,3'-dichlorobenzidine, azodicarbonamide and tert-butyl perbenzoate to a mixed solvent of glycerol and ethanol to form a polycondensation reaction solution; b2. Immerse the intermediate A in the polycondensation reaction solution, heat to 45-60°C in a water bath under magnetic stirring, and react for 3-5 hours to complete the polycondensation reaction of benzocyanate diisocyanate and dichlorobiphenyl, and obtain a foam copper with benzocyanate dichlorobiphenyl polyurea loaded on the surface, which is recorded as intermediate B.

6. The method for preparing a foam copper-based adsorbent material for treating wastewater containing mercury ions according to claim 5, characterized in that: The volume ratio of glycerol to ethanol in the mixed solvent is 1-2:3-4; the amount of 3,3'-dichlorobenzidine added to each liter of the polycondensation reaction liquid is 240-270 g, the amount of azodicarbonamide added is 50-70 g, and the amount of tert-butyl perbenzoate added is 20-40 mL.

7. The method for preparing a foam copper-based adsorbent material for treating wastewater containing mercury ions according to claim 5, characterized in that: In step b2, the weight of the intermediate A immersed in each liter of the polycondensation reaction liquid is 80-130 g; and the stirring speed is 90-130 rpm.

8. The method for preparing a foam copper-based adsorbent material for treating wastewater containing mercury ions according to claim 1, characterized in that: The step [3] specifically includes the following operations: c1. Add ammonium thiosulfate and dimethyl sulfoxide to deionized water and mix to form a chlorine substitution solution; immerse the intermediate B in the chlorine substitution solution and allow the reaction to proceed at room temperature for 6-8 hours to complete the chlorine substitution process of the thiol group to obtain an intermediate C; c2. Add hydroxylamine and ethylenediamine to deionized water and mix to form an amidoxime group-forming liquid; immerse the intermediate C in the amidoxime group-forming liquid and react at room temperature for 7-9 hours to complete the formation process of the amidoxime group, and obtain a foam copper with amidoximephenyl dimercaptobiphenyl polyurea loaded on the surface, which is the adsorption material.

9. The method for preparing a foam copper-based adsorbent material for treating wastewater containing mercury ions according to claim 8, characterized in that: In step c1, the concentration of ammonium thiosulfate in the chlorine substitution liquid is 140 g / L-180 g / L, and the concentration of dimethyl sulfoxide is 70 mL / L-100 mL / L; the weight of the intermediate B immersed in each liter of the chlorine substitution liquid is 150-170 g.

10. The method for preparing a foam copper-based adsorbent material for treating wastewater containing mercury ions according to claim 8, characterized in that: In step c2, the concentration of hydroxylamine in the amidoxime group forming liquid is 210g / L-230g / L, and the concentration of ethylenediamine is 30mL / L-60mL / L; the weight of the intermediate C immersed in each liter of the amidoxime group forming liquid is 70-90g.

Citation Information

Cited By

  • Preparation method of foamy copper-based catalytic material for electrochemical degradation of chloramphenicol sewage

    CN119857534A